Is equipment price deflation a statistical artifact? - Bart Hobijn (Federal Reserve Bank of New York, 2001)
I argue that equipment price deflation might be overstated because the methods used to measure it rely on the erroneous assumption of perfectly competitive markets. The main intuition behind this argument is that what these price indices might actually capture not a price decrease but the erosion of the market power of existing vintages of machines. To illustrate my argument, I introduce an endogenous growth model in which heterogeneous final goods producers can choose the technology they will use. The various technologies are supplied by monopolistically competing machine suppliers. This market structure implies that the best machines are marketed to the best workers and are sold at the highest markup. In my model economy, the endogenously determined markups are such that standard methods will tend to find equipment price deflation, even though the model does not exhibit any equipment price deflation.
Keywords: O310; O470; C190; 330; imperfect competition; price indices; vintage capital; Investitionsgut; Deflation; Messung; Hedonischer Preisindex; Computer; Theorie; USA